GAMBARAN KEJADIAN DEPRESI POSTPARTUM DI PUSKESMAS PEKANBARU - Sari, Lispitri Mayang; Misrawati, Misrawati; Rizka, Yulia (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
Women will experience physiological and psychological changes after giving birth, these changes can cause stress on the mother due to adjustment demands due to ongoing life changes. This study aims to describe the incidence of postpartum depression at the Pekanbaru City Health Center. The design used in this research is simple descriptive using purposive sampling technique and the sample used is 79 respondents. The sample used was postpartum mothers 10 days to 6 months. This study used the Edinburgh postnatal depression scale (EPDS) questionnaire which uses a cut-off of 10, meaning that a score of ≤9 means that you do not tend to experience depression, while a score of ≥10 means that the respondent tends to experience depression. The results showed that 64 respondents (81.0%) did not tend to experience depression and 15 respondents (19.0%) tended to experience depression. After giving birth, many mothers are not aware of the symptoms of depression that occur, for this reason the importance of health education and depression screening programs or early detection after delivery to prevent postpartum depression.